Üsküp Mustafa Paşa Camii Haziresi'ndeki Mezartaşları - Tunçel, Gül (Dinî araştırmalar, 2005)
In Skopje Mustafa Paşa Mosque Graveyard the material, design and decoration of four gravestones and two graves in the shape of sarcophagus have been clarified and it was tried to identify their artistic characteristics and their place in Turkish art by comparing them with other Ottoman gravestones